PLANETARY ETHICS DURING ANTHROPOCENE - Nandhikkara, Jose (Journal of Dharma, 2021)
COVID-19 has given us a clear indication of the vulnerability and fragility of modern life and the modern world; it has also taught that we can overcome planetary challenges only by showing solidarity with one another and embracing the most vulnerable in our midst - one Earth and one health. The global pandemic and climate change cannot be separated from hunger, health, education, migration, war, employment, and development. Though as human beings we have our unique identity, we also form part of the universe with the rest of the world, who are neither strangers to us nor our enemies but actually our neighbours and fellow partners on this planet without whom the sustenance of human life is impossible. We need a Theanthropocosmic vision to embrace and expand our worldviews to include more and more the natural world. We cannot afford to leave the natural resources of the earth to those who have the technology to exploit them, and money to purchase them. Together with science and technology, humanities, social sciences, traditional knowledge, philosophical wisdom, and religious traditions contribute to the prosperity and peace for People and Planet. Investigating these sources of knowledge, this issue of the Journal of Dharma includes eight articles that show case the inter-connections of the prosperity and peace of People and Planet.